Incomplete pentalogy of Cantrell in a Border terrier puppy. Issue 4 (29th October 2020) - Williams, Phillipa; Booth, Malcolm; Rossanese, Matteo
Abstract : A 4‐month‐old, 6.4‐kg, male entire, Border terrier was referred for investigation of exercise intolerance and a suspected congenital midline defect. Physical examination revealed a sternal and a supraumbilical abdominal defect. Thoracic radiography and CT confirmed a congenital sternal cleft, a large supraumbilical diastasis rectus and a pleuroperitoneal diaphragmatic hernia. No congenital cardiac defect was detected during echocardiographic examination. These findings were consistent with an incomplete Cantrell's pentalogy. Surgical reconstruction involved diaphragmatic reconstruction, abdominal muscle herniorrhaphy and novel closure of a sternal cleft with crimped monofilament nylon leader line. The dog had grown since surgery to a mature adult size and did not exhibit exercise intolerance 18 months postoperatively. Cantrell's pentalogy is a collection of congenital midline defects that are rare in the dog and cat but can be successfully treated surgically, especially if diagnosed at a young age and if not involving intracardiac defects.